ANTIOXIDANT MODULATION OF THE RYFA SRNA STRESS AXIS TO RE-SENSITIZE UROPATHOGENIC ESCHERICHIA COLI TO CIPROFLOXACIN: VITAMIN C AS AN ADJUVANT - RAJAPPAYYA T DESAI; ANNAPURNA SAJJAN; SUNEEL I MAJAGI; AKRAM NAIKWADI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: To test whether Vitamin C (ascorbate) at urinary-plausible concentrations can re-sensitize ciprofloxacin-resistant uropathogenic Escherichia coli (UPEC) in a simple agar model, and to interpret any adjuvant signal through the RyfA small-RNA oxidative-stress axis. Methods: In vitro Kirby–Bauer testing on Mueller–Hinton agar (35–37°C) using ciprofloxacin-resistant UPEC CFT073. Arms: Media control, Vitamin C 5 or 10 mg/mL alone, ciprofloxacin 5 μg alone, and combinations (ciprofloxacin disc spotted with 10 μL Vitamin C solution). Triplicate plates per arm were read at day-1/3/5 by two blinded readers. The primary endpoint was day-5 zone size for combination arms versus a 0 mm reference (ciprofloxacin-alone remained 0 mm). One-sample t-tests (α=0.05) were applied; reads beyond 24 h were treated as exploratory kinetics. Results: Vitamin C alone yielded 0 mm at all time points; ciprofloxacin alone also remained 0 mm. Ciprofloxacin+Vitamin C produced measurable halos that increased over time. Day-5 means (±standard deviation) were 15.1±0.8 mm for 5 mg/mL and 15.9±0.9 mm for 10 mg/mL (both p<0.05 vs. 0 mm). Kinetics showed early growth with 5 mg/mL (8.8 mm day-1; 10.2 mm day-3), whereas 10 mg/mL lacked an early halo but converged by day-5. A modest dose trend was suggested but not formally tested. Conclusion: In this single-strain, in-vitro, ascorbate at 5–10 mg/mL restored measurable ciprofloxacin activity against a ciprofloxacin-resistant reference UPEC strain (CFT073) in an agar system, consistent with attenuation of a RyfA-linked oxidative-stress program. These proof-of-concept findings require confirmation in broader clinical strain panels, MIC/time-kill assays in urinary matrices, and RyfA-axis expression studies before any clinical extrapolation.